Resistensi Pendidikan Madrasah dI Yasinat Jember (Studi Kasus Pada Madrasah Berbasis Pesantren Salaf) - Ridho, Akhsin; Damairi, Muhammad Uzaer (Program Studi Pendidikan Agama Islam, Universitas Muhammadiyah Bandung, 2024)
This study aims to examine the resilience of education in Pesantren-based Madrasahs in Yasinat, Jember. The primary focus is to understand how these madrasahs sustain their existence in the face of various challenges, including social, economic, and technological changes. The research employs a case study approach with qualitative methods, collecting data through interviews, observations, and documentation. The findings indicate that the Pesantren-based madrasahs in Yasinat exhibit strong resilience, driven by the essential role of traditional values, active community involvement, and adaptations to technological advancements and educational curricula. The conclusion of this study is that despite facing challenges, the Pesantren-based madrasahs possess significant resilience to maintain educational quality and social relevance.